2015
DOI: 10.1109/twc.2014.2362523
|View full text |Cite
|
Sign up to set email alerts
|

Group Partition and Dynamic Rate Adaptation for Scalable Capacity-Region-Aware Device-to-Device Communications

Abstract: In this paper, we propose using group partition and dynamic rate adaptation for scalable throughput optimization of capacity-region-aware device-to-device communications. We adopt network information theory that allows a receiving device to simultaneously decode multiple packets from multiple transmitting devices, as long as the vector of transmitting rates is inside the capacity region. Based on graph theory, devices are first partitioned into subgroups. To optimize the throughput of a subgroup, instead of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Moreover, [57] claimed that the network capacity can be enhanced by increasing the density of D2D users, whilst our findings can provide an additional perspective for [57] by taking into account the topology of D2D network. In social networks, [58] showed that traffic distribution and network capacity can be analyzed by representing a social network as a human contact graph, and further works can be done by characterizing the graph as a fractal network.…”
Section: B Contributionmentioning
confidence: 99%
“…Moreover, [57] claimed that the network capacity can be enhanced by increasing the density of D2D users, whilst our findings can provide an additional perspective for [57] by taking into account the topology of D2D network. In social networks, [58] showed that traffic distribution and network capacity can be analyzed by representing a social network as a human contact graph, and further works can be done by characterizing the graph as a fractal network.…”
Section: B Contributionmentioning
confidence: 99%
“…which is easy to implement in a distributed fashion but is static and often over-restrictive, nor on a centralized optimization problem, as in [9], [12], [15], [16], which achieves optimal solutions, but needs full channel state information over all the involved channels.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in [18] defined a scheme to forward interference by means of D2D communications, in order to make it easier to apply interference cancellation schemes; similarly, in [19] the BS relays the D2D communications to allow interference cancellation at the receiving nodes. In [16], graph theory is used to divide mobiles into subgroups, and a throughput maximization is attained by employing multiuser detection and solving an iterative optimization algorithm. In [20] contract theory is leveraged to study the incentives to be granted to potential D2D users.…”
Section: Related Workmentioning
confidence: 99%